Dampak Stress Akademik terhadap Integrasi Sosial pada Mahasiswa Rantau - Stanley Darwinus Jayadi; Meike Kurniawati (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to examine the impact of academic stress levels on the ability of non-local (migrant) students to achieve social integration. The research is motivated by the urgency of understanding how academic pressures experienced by students influence their social adaptation processes, particularly for those living far from their home environments and families. Migrant students often face dual challenges: high academic demands and the need to adjust to a new social environment with different cultures, habits, and social interactions. Using a quantitative approach and a correlational method, a specially designed questionnaire was distributed to obtain data measuring academic stress levels and students' social integration abilities. The data were then analyzed using Pearson’s correlation analysis to identify the relationship between the two variables. The findings indicate a significant negative effect between academic stress and social integration. This suggests that higher levels of academic stress among students are associated with lower capacities for social integration. These results highlight the importance of interventions in the form of academic and psychosocial support both from educational institutions and families to facilitate a more effective and comprehensive social adaptation process for migrant students.